Pengaruh Electronic Word Of Mouth (E-Wom) dan Online Customer Experience terhadap Keputusan Pembelian Produk Skintific di Shopee - Salma Mayviana Zahrani; Ambardi Ambardi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The growth of e-commerce in Indonesia has changed consumption patterns, especially in the online purchase of skincare products. Shopee, as the largest marketplace, has become the main platform for brands such as Skintific, which has achieved high sales. This phenomenon shows the support of online consumer reviews (Electronic Word of Mouth/E-WOM) and digital shopping experiences (Online Customer Experience/OCE). This study aims to examine the influence of E-WOM and OCE on purchasing decisions for Skintific products on Shopee. This study used a quantitative method with an associative approach. The research sample consisted of 97 respondents obtained through purposive sampling. Data analysis was performed through validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results of the study indicate that E-WOM has a positive and significant effect on purchasing decisions (calculated t = 5.209 > table t = 1.986; sig. <.001). OCE also has a positive and significant effect on purchasing decisions (t-count = 7.605 > t-table = 1.986; sig. <.001). Simultaneously, both independent variables have a significant effect on purchasing decisions (F-count = 101.366 > f-table = 3.09; sig. <.001). The coefficient of determination (R²) value of 0.683 indicates that 68.3% of the variation in purchase decisions can be explained by E-WOM and OCE, while the remaining 31.7% is influenced by other factors outside the research model. These findings confirm that consumer online reviews and positive online shopping experiences play an important role in increasing purchase decisions for Skintific products on Shopee.